Parallel Calculation of Properties of Magnetic Impurities in Metais - Sonoda, Eloiza; Travieso, Gonzalo (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2001)
The computation of physical properties of dilute magnetic alloys is a computationally intensive task. In principie, it consists on the diagonalization of a huge matrix. Through the use of a suitable base and of the renormalization group method, the diagonalization can be simplified to the iterative diagonalization of a set of smaller matrices (of the order of some hundreds of lines and columns). The resulting problem is nevertheless still too large if enough precision is desired. We describe here the parallel implementation of an algorithm for this problem in a duster. The results show that the implementation achieves good reduction of execution times, but lacks speedup and scalability due to load balancing problems. We analyze these problems and suggest paths to their resolution.